Some Aspects of the Dynamics of a Hunted Bobwhite Population - John L. Roseberry; W. D. Klimstra (National Quail Symposium Proceedings, 2017)
Dynamics of a hunted bobwhite population have been investigated on a 1,450-acre study area near Carbondale, Illinois since 1952. Habitat conditions have not changed greatly during the study, and November densities have oscillated regularly about a rather stable long-term mean. Most of the variance of annual rates of population change is due to variation in net productivity from spring to fall rather than to variation in net losses from fall to spring. Population declines from November to April averaged 66% (range 36 to 81%); about 0.66 of this resulted from hunting. Post-hunting mortality, which was slightly density-related, partially compensated for hunting losses. Spring densities were correlated with (r = +o.75) and almost as variable as preceding fall populations. Net increases from spring to fall varied from 17 to 383 and averaged 235% of the breeding population. Multiple regression analysis showed that annual rates of productivity were significantly influenced by the combined effect of breeding density, length of snow cover during the previous 2 winters, and amounts of prenesting rainfall. Annual rates of population change were inversely related to the preceding fall density, but strong correlations between successive seasonal population levels caused periods of change as well as highs and lows to persist for several years. Major highs and lows each occurred at 8- to 10-year intervals. It was not clear whether 2 severe winters caused the apparent cyclic regularity or merely accentuated the lows.